Traffic related air pollution and the burden of childhood asthma in the contiguous United States in 2000 and 2010. (June 2019) - Alotaibi, Raed; Bechle, Mathew; Marshall, Julian D.; Ramani, Tara; Zietsman, Josias; Nieuwenhuijsen, Mark J.; Khreis, Haneen
Abstract: Background: Asthma is one of the leading chronic airway diseases among children in the United States (US). Emerging evidence indicates that Traffic Related Air Pollution (TRAP), as opposed to ambient air pollution, leads to the onset of childhood asthma. We estimated the number of incident asthma cases among children attributable to TRAP in the contiguous US, for the years 2000 and 2010. Methods: The number of incident childhood asthma cases and percentage due to TRAP were estimated using standard burden of disease assessment methods. We combined children (<18 years) counts and pollutant exposures at populated US census blocks with a national asthma incidence rate and meta-analysis derived concentration response functions (CRF). NO2, PM2.5 and PM10 were used as surrogates of TRAP exposures, with NO2 being most specific. Annual average concentrations were obtained from previously validated land-use regression (LUR) models. Asthma incidence rate and a CRF for each pollutant were obtained from the literature. Estimates were stratified by urban or rural living and by median household income. We also estimated the number of preventable cases among blocks that exceeded the limit for two counterfactual scenarios. The first scenario used the recommended air quality annual averages from the World Health Organization (WHO) as a limit. The second scenario used the minimum modeled concentration for each pollutant, in either year, as a limit. Results: Average concentrations in 2000 and 2010, respectively, were 20.6 and 13.2 μg/m 3 for NO2, 12.1 and 9 μg/m 3 for PM2.5 and 21.5 and 17.9 μg/m 3 for PM10 . Attributable number of cases ranged between 209, 100–331, 200 for the year 2000 and 141, 900–286, 500 for 2010, depending on the pollutant. Asthma incident cases due to TRAP represented 27%–42% of all cases in 2000 and 18%–36% in 2010. Percentage of cases due to TRAP were higher (1) in urban areas than rural areas, and (2) in block groups with lowest median household income. Online open-access interactive maps and tables summarizing findings at the county level and 498 major US cities, are available at [https://carteehdata.org/l/s/TRAP-burden-of-childhood-asthma ]. Assuming that pollutants did not exceed WHO air quality recommendations, the number of incident cases that could have been prevented ranged between 300 and 53, 400, depending on the pollutant and year. Assuming that pollutant levels were limited to the minimum modeled concentration, the number of childhood asthma incident cases that could have been prevented ranged between 127, 700 and 317, 600, depending on the pollutant and year. Conclusion: This is the first study to estimate the burden of incident childhood asthma attributable to TRAP at a national scale in the US. The attributable burden of childhood asthma dropped by 33% between 2000 and 2010. However, a significant proportion of cases can be prevented. Highlights: 141, 900-331, 200 of asthma cases were attributable to traffic related air pollution 18%-42% of asthma cases were attributable to traffic related air pollution Urban areas had up to twice the burden of asthma as compared to rural areas Attributable number of cases reduced by up to 33% between 2000 and 2010 Our approach could lead to an overestimation of the burden of asthma "due to traffic-related air pollution"